Cysteine redox proteomics of the hemoglobin‐depleted cytosolic fraction of stored red blood cells. Issue 8 (6th August 2016) - Delobel, Julien; Prudent, Michel; Crettaz, David; ElHajj, Zeinab; Riederer, Beat M.; Tissot, Jean‐Daniel; Lion, Niels
Abstract : Purpose: Erythrocyte concentrates (ECs) represent the most transfused labile blood products. They are stored at 4°C in additive solutions for up to 56 days. Protein oxidation is a marker of oxidative stress and cysteine residues, whose oxidations are required for physiological cell functions, are highly prone to such modification. Experimental design: Five ECs from independent donations were followed. Soluble protein extracts were prepared at days 6, 27, and 41, and cysteines were alkylated, reduced, and labeled with infrared dyes. Samples were mixed two by two (day 6 as reference) and analyzed by 2D‐DIGE. Detection of labeled cysteines allows quantitative comparison of oxidative status. Spots of interest were analyzed by proteomics. Results: Thirty‐two spots containing 43 proteins were classified as increasing, decreasing, or exhibiting a peak of expression during storage. Proteins having catalytic and antioxidant activities were particularly affected during storage, for example, peroxiredoxin‐1 and DJ‐1 were reversibly oxidized and catalase was irreversibly oxidized. These proteins could be used to evaluate different storage strategies to maintain proper protein function during the overall storage period. Conclusions and clinical relevance: This redox‐DIGE approach brings new quantitative data on oxidized proteins in stored red blood cells. As previously reported on carbonylation, the oxidative damages differently affect protein functions.